Synthesis And Characterization of 5-(Mercapto-1,3,4Thiadiazole-2yl)Î±,Î±-Diphenyl Methanol From Benzilic Acid - Mahmoud, Muhanned J.; AL-bayati, Redha I.; Saoud, Shaimaa A.; Majeed, Ismaeel Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
5-(mercapto-1,3,4-thiadiazole-2yl)Î±,Î±-(diphenyl)methanol have been synthesized by ring closer of potassium xanthate[which have been prepared by reaction of benzilic acid hydrazide with carbon disulphide in potassium hydroxide] using conc.sulphuric acid at (0-5)Â°C scheme(I). Their characterization was carried out from T.L.C, M.P, FT.IR and 1H-NMR.